Structural Properties of Cs1+ Doped H3PMo12O40 Nanocrystalline Polyoxometalate Thin Films - Prashant B. Patil,; Bajarang B. Patil,; Tukaram J. Shinde,; Sambhaji R. Mane, (International Journal of Scientific Research in Science and Technology, 2024)
The microwave assisted chemical bath deposition (MA-CBD) technique were used to deposite nanocrystalline thin films of polyoxometalates like phosphomolybdic acid (PMA) (H3PMo12O40) and Cesium (Cs+) doped phosphomolybdic acid (Cs-PMA) (Cs3-PMo12O40). Thermo gravimetric and Differential thermal analysis (TGDTA), Fourier transform infrared spectroscopy (FTIR), Energy dispersive X-ray analysis (EDAX), X-ray diffractometry (XRD) and Scanning electron microscopy (SEM) tools are used for the thermal, structural, morphological and compositional analysis of microwave treated H3PMo12O40 and Cs3- PMo12O40 thin films. The completion of decomposition process at 600 oC of Cs3-PMo12O40 compound is confirmed from TGDTA analysis. The polycrystalline spinel cubic crystal structure of H3PMo12O40 and Cs3-PMo12O40 thin films were confirmed from X-ray diffractometer. The crystallite size of H3PMo12O40 and Cs3-PMo12O40 compound found to be in the range of 50 - 53 nm. The formation of H3PMo12O40 and Cs3-PMo12O40 materials were confirmed from the presence of main four absorption peaks observed in the range from 800 cm-1 to 1100 cm-1. The SEM microphotographs analysis identify the microwave assisted H3PMo12O40 and Cs3-PMo12O40 films have spherical shaped porous nanocrystalline morphology. The grain size of H3PMo12O40 and Cs3-PMo12O40 synthesized material found to be in the range of 10 - 12 A˚ The stoichiometric preparation of H3PMo12O40 and Cs3-PMo12O40 thin films with presence of P, Mo, O and Cs peaks of metal ions is observed from EDAX spectra.
Keywords: Cs doped PMA; MACBD; TGDTA; XRD; FTIR; SEM; EDAX